2021
DOI: 10.1097/qai.0000000000002777
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Social and Spatial Closeness With PrEP Conversations Among Latino Men Who Have Sex With Men

Abstract: Background: US Latino men who have sex with men (LMSM) are a group at highest risk for HIV. One driver of HIV among LMSM is inadequate access to pre-exposure prophylaxis (PrEP) information. The social network theory of homophily suggests that sharing similar sociodemographic factors could influence PrEP conversations within networks. This study aimed to determine how the effects of homophily across sociodemographic, immigration, cultural, and PrEP-related factors are associated with PrEP-related communication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The program reached critical populations for HIV testing and PrEP information dissemination; 16.2% reported no previous HIV test, and 38.5% reported never having heard about PrEP for HIV prevention before receiving the Test-to-PrEP kit. This work expands upon past studies that found social networks to be successful modes for information distribution [24][25][26] by demonstrating that social networks facilitate Test-To-PrEP kit distribution and successfully reach and educate individuals who previously lacked PrEP knowledge. To our knowledge, this is the first study to use a social network-based strategy for the distribution of HIVST kits by current PrEP users.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The program reached critical populations for HIV testing and PrEP information dissemination; 16.2% reported no previous HIV test, and 38.5% reported never having heard about PrEP for HIV prevention before receiving the Test-to-PrEP kit. This work expands upon past studies that found social networks to be successful modes for information distribution [24][25][26] by demonstrating that social networks facilitate Test-To-PrEP kit distribution and successfully reach and educate individuals who previously lacked PrEP knowledge. To our knowledge, this is the first study to use a social network-based strategy for the distribution of HIVST kits by current PrEP users.…”
Section: Discussionsupporting
confidence: 66%
“…Prior work has largely focused on identifying peer leaders and the importance of peer influence on PrEP information dissemination. 24,35,36 Our findings indicate the importance of peer groups with whom individuals can share and engage in conversations on sensitive topics, such as PrEP use and HIV testing. Our work suggests that clients recently initiated in PrEP care may be a powerful source of PrEP information and intervention proliferation.…”
Section: Discussionmentioning
confidence: 82%
“…Many sexual minorities are migrating to the U.S., regardless of documentation status, for opportunities to work, to increase their quality of life, and to experience the freedom to express their sexual orientation and gender identity ( American Psychological Association, 2019 ; Cerezo et al, 2014 ). This change in geographic space often coincides with significant changes in social space as well, such as whether, where, and how individuals access social support, family interactions, sexual health communication or engaging with health promotion services ( Diaz, 1997 ; Shrader et al, 2021 ). An understudied social process that may determine variable HIV risk, testing, and linkage to care is geographic mobility, especially among Latinx migrant MSM.…”
Section: Introductionmentioning
confidence: 99%